Development of Electronic Soccer Goalkeeper Reaction Speed Training Equipment 2020 - Tarigan, Reky Wijayandaru; Siregar, Irwansyah (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2021)
This study aims to determine the feasibility of the 2020 Electronic Football Goalkeeper Reaction Speed Training Tool. This research method is a type of Research and Development (R&D). The subjects of this research were taken from SSB Perstas, SSB Kwarta, and SSB Cakra. Development of the Electronic-Based Soccer Goalkeeper Reaction Training Tool for 2020 has been made and validated by 4 experts, namely Equipment, Electronics, Coach, and Sports. The results of the small group test involving 9 goalkeepers from SSB Perstas, SSB Patmi 50, and SSB Cakra, show that the goalkeeper reaction speed training tool meets the criteria to be continued in large group trials with a percentage of 84 - 100%. The results of the large group test involving 15 goalkeepers from SSB Perstas, SSB Patmi 50, SSB Cakra SSB Kwarta and SSB Gumarang, showed that the goalkeeper reaction speed training tool met the criteria to be continued into mass production with a percentage of 82-100%. It can be concluded that the development of a football goalkeeper reaction speed tool can be categorized as